Biopotential of Gorontalo Hulu’u Fish (Giuris margaritacea) Albumin in a Novel Spray Gel Formulation for the Treatment of BurnWounds: In Vivo Evaluation in Rats - Paneo, Mohamad Aprianto; Djuwarno, Endah Nurrohwinta; Habibie, Sitty Ainsyah; Thomas, Nurain; Latif, Multiani S.; Munafri, Nur Alifia Karina; Anasiru, Rayhan Firman (Science and Technology Indonesia, 2026)
This study aimed to evaluate the efficacy of different concentrations of Hulu’u fish albumin-based spray gels in promoting wound healing in burn injuries in male white rats. The formulations included 10%, 15%, and 20% concentrations of Hulu’u fish albumin, which were compared to a commercial snakehead fish albumin gel (positive control) and a spray gel base without albumin (negative control). Wound diameter reduction was assessed over seven days. The results indicated a clear dose response relationship, with the 20% Hulu’u fish albumin formulation (F3) achieving the most significant reduction in wound diameter, averaging 1.57 mm (range: 1.5–1.6 mm), representing a 91.8% improvement compared to the negative control group, which showed an average reduction of 19.13 mm (range: 18.1–19.7 mm). The Positive Control (snakehead fish albumin gel) demonstrated a moderate reduction with an average of 6.97 mm (range: 6.6–7.6 mm). The 10% Hulu’u fish albumin (F1) and 15% Hulu’u fish albumin (F2) formulations showed moderate improvements, with average reductions of 4.73 mm (range: 4.4–5.1 mm) and 4.5 mm (range: 4.7–3.9 mm), respectively. These findings suggest that higher concentrations of Hulu’u fish albumin, particularly the 20% formulation, offer superior wound healing properties, outperforming both the negative control and the commercial snakehead fish albumin gel. The study highlights the potential of Hulu’u fish albumin as a novel bioactive compound for burn wound treatment and warrants further investigation for clinical applications.